The impact of foreign financial inflows on the economic growth of sub-Saharan African countries: An empirical approach - Belesity Bekalu Ayenew (Cogent Economics & Finance, 2022)
The impact of foreign financial inflows on the economic growth of recipient countries is a controversial issue in many empirical studies. The majority of the previous studies use one variable as an indicator of foreign financial inflows; they fail to incorporate many variables. The study fills this gap by using remittance inflows, foreign direct investment, official development assistance, and external debt as an indicator of foreign financial inflows. This study investigates the impact of foreign financial inflows on the economic growth of 31 sub-Saharan African countries over the period 2009 to 2019. The study employed a two-step system GMM due to its practical advantage on the dynamic panel data set. The finding shows that only foreign direct investment has a significant and positive contribution to economic growth. Official development assistance and external debt affect economic growth negatively, and they are statistically significant. Remittance inflow affects economic growth negatively, but it is statistically insignificant. The study suggests that policymakers should work on the way that remittance inflow promotes investment and reduce dependency on official development assistance. In addition, external borrowing should be used for productive purposes.
Keywords: F02; F15; F24; F35; F41; O55; 330; Foreign direct investment; economic growth; remittance; official development assistance; external debt; sub-Saharan Africa